Sustainable Development Goals (SDGs), Socio Environment and Socio Education - Syamsiah Badruddin; Paisal Halim; Muhammad Ikhsan Setiawan; Agus Sukoco; Muhammad Isradi; Sugeng Sugeng; Fajar Prihesnanto; Abdul Talib Bon (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The 2023 Global Sustainable Development Report will be launched as the world approaches the half-way point of the 2030 Agenda and struggles to rebuild in the aftermath (or in the midst) of the COVID-19 pandemic. Compare the document counts for up to 15 sources, year 2020 until 2021, there are increase of documents based on Sustainable Development Goals (SDGs), Socio Education documents published in SCOPUS.COM. Subject area dominant is Social Sciences, followed by Environmental Science, Medicine. Design/methodology/approach: Source Documents dominant is International Journal Of Emerging Technologies In Learning, followed by Sustainability Switzerland, E3s Web Of Conferences, and Lancet. There are no Indonesia journal. By country or territory, Nigeria, United Kingdom, and India dominant in the World. In Malaysia, very strong, followed by Viet Nam, Indonesia, Philippines, Singapore, Myanmar, and Thailand. By funding sponsor, dominant Bill and Melinda Gates Foundation, followed by Covenant University, Covenant University Centre for Research, Innovation and Discovery, European Commission, and Fundação para a Ciência e a Tecnologia. There are no Indonesia funding sponsor. By affiliations, dominant James Cook University, followed by Organisation Mondiale de la Santé, Lunds Universitet, and University of Cape Coast Ghana. There are no Indonesia affiliations. Compare the document counts for up to 15 sources, year 2020 until 2021, there are increase of documents based on Sustainable Development Goals (SDGs), Socio Environment documents published in SCOPUS.COM. Findings: Subject area dominant is Social Sciences, followed by Environmental Science, Energy. Source Documents dominant is Energy Reports journal, followed by Sustainability Science journal, International Organisations Research Journa, Smart Innovation Systems And Technologies journal, and Sustainability Switzerland journal. There are no Indonesia journal. By country or territory, United Kingdom dominant, followed by South Africa and Nigeria. In ASEAN dominant Indonesia and Malaysia. By funding sponsor, Bill and Melinda Gates Foundation dominant, followed by Bundesministerium für Bildung undForschung, Centre for International Forestry Research, European Commission, and European Social Fund. None from Indonesia. By affiliations, University of KwaZulu-Natal dominant, followed by Dokuz Eylül Üniversitesi, South African Water Research Commission, University of Venda, and Russian Presidential Academy of National, from Indonesia there is Universitas Indonesia, Universitas Indonesia, 29,793 documents, whole institution, 28,845 documents, affiliation only, 17,394 Authors, Document count (high-low), Medicine 7,069 docs, Engineering 5,685 docs, and Physics and Astronomy 5,145 docs. Universitas Indonesia research publication connected with Sustainable Development Goals (SDGs), Socio Environment. Paper type: Research paper